Technical Guidance on Attendance List Management Applications and Updating SIASN Data for Civil Servant Lecturers - Zulkifli, Zulkifli; Bintoro, Panji; Yana Ayu Andini, Dwi; Eko Setiawan, Agustinus; Herdia Andika, Tahta; Ardhy, Ferly (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: The implementation of the AMANDA (Attendance Management and SIASN Data Updating Application) has significantly improved educational administration, especially for civil servant lecturers. Contribution: AMANDA serves as a model for future public sector innovations, improving efficiency, accountability, and adaptability. Method: The background to the development of this application comes from challenges in manual processes which tend to be time consuming, prone to errors, and less efficient in terms of data processing. Results: It has reduced time spent on administrative tasks by 30% and decreased errors by 25%, enhancing accuracy and efficiency. User feedback has been positive, with 85% of lecturer satisfied, highlighting its ease of use. Conclusion: The application has also demonstrated the power of digital tools to streamline operations, improve data integrity, and promote user engagement. Furthermore, user satisfaction and training outcomes suggest that continued investment in technology and training is essential for optimizing administrative processes.